Islamic Religious Education in the Digital Era: Between Transhuman Pedagogy and Digital Spiritual Education - Agung Nugroho; Salamah Salamah; Fahmi Hamdi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The transformation of education in the era of the Fourth Industrial Revolution has intensified human–technology integration through artificial intelligence, adaptive learning systems, and pedagogical automation. While these developments enhance efficiency, personalization, and measurable learning outcomes, they also raise fundamental ethical concerns regarding pedagogical relationships, learner autonomy, and human dignity. This article examines transhuman pedagogy and digital spiritual education as two dominant trajectories shaping contemporary digital education and nalyses the strategic role of Islamic Religious Education (IRE) in bridging these paradigms. This study employs a conceptual literature-based approach using argumentative and thematic analysis of scholarly works on transhumanism in education, digital pedagogy, and spiritual education from an Islamic perspective. The analysis indicates that transhuman pedagogy offers significant potential for cognitive optimization and personalized learning but risks reducing education to a functional human–technology relationship that weakens the formation of learners as dignified moral subjects. Conversely, digital spiritual education expands access to religious learning and always-connected spiritual experiences but tends to generate fragmented, performative, and superficial spirituality when detached from deep reflection and ethical formation. The article argues that Islamic Religious Education should be positioned as an axiological and ethical framework that guides the use of educational technology toward faith-based values, moral integrity, and human dignity. Practical implications include strengthening value-oriented IRE curricula, implementing reflective–critical pedagogical methods, reinforcing the role of IRE teachers as moral–spiritual mediators, and integrating spiritual values within school digital ecosystems. In this way, Islamic Religious Education functions as a space of synthesis that positions technology as a means rather than an end in the holistic formation of human beings in the digital age.